LIQUID WASTE MONITORING SECURITY SYSTEM BASED ON THE INTERNET OF THINGS AND PROTECTED BY WIREGUARD - Pratama, Bagus Gilang; Qodri, Muhammad Fatih (KURVATEK, 2023)
Water has become one of the most important human needs, especially in rivers related to industrial waste processing. Parameters of liquid waste quality that are closely related to human life are pH levels, Total Dissolve Solids (TDS), and water temperature. With the advancement of information technology, smart solutions for water quality monitoring are becoming more popular. This research aims to build a liquid waste quality monitoring system from the plastics industry based on Internet of Things (IoT) technology and protected by Wireguards. The monitoring system is designed using an Analog pH Meter Sensor to measure pH, a TDS Meter Sensor to measure the dissoved level of liquid waste, and a DS18B20 Sensor to measure water temperature. The design of this system uses a wifi network connected to the internet to send sensor data to the data center. To prevent data from being read by irresponsible parties, the system is integrated with Wireguard VPN, so that all data sent from the monitoring system will be perfectly encrypted and can only be opened by clients who have the key. The results of the sensor readings that have been sent to the data center can be accessed by authenticated users via a website that can be accessed via a smartphone application or laptop browser. Based on the test results, the monitoring system can work well to manage liquid waste in the plastics industry. Furthermore, if there are unfavorable results for the environment regarding liquid waste from the measurement results, it can be handled quickly and efficiently.